Assessing the utility of the Movement Disorder Society Task Force Level 1 diagnostic criteria for mild cognitive impairment in Parkinson's disease. Issue 1 (January 2015) - Szeto, Jennifer Y.Y.; Mowszowski, Loren; Gilat, Moran; Walton, Courtney C.; Naismith, Sharon L.; Lewis, Simon J.G.
Abstract: Background: Using the Movement Disorder Society (MDS) Task Force Level 1 criteria, this study examined the classification of mild cognitive impairment in Parkinson's Disease (PD-MCI) derived from a range of cut-off scores that have previously been suggested by the MDS Task Force. Furthermore, differences in PD-MCI frequencies were examined when comparing performance on current neuropsychological testing to the normative sample, as opposed to decline from premorbid functioning, as evidence of cognitive impairment. Method: Two hundred and thirty-four non-demented PD patients underwent neurological and neuropsychological assessment at the Parkinson's Disease Research Clinic at the Brain and Mind Research Institute, University of Sydney. Results: When cognitive impairment was defined as 1SD and 1.5SD below premorbid intellect, 109 patients (47%) and 76 (32%) patients met criteria for PD-MCI respectively. This proportion dropped considerably to 50 patients (21%) with a 2SD cut-off score. However, when calculating impairment based on comparisons with normative data, only 68 patients (29%) and 41 patients (18%) met PD-MCI criteria when a cut-off score of 1 and 1.5SD was employed. This proportion dropped to just 22 patients (9%) with a 2SD cut-off score. Conclusion: Results from the present study suggest that the MDS PD-MCI criteria may be too broad, as substantial differences in frequencies of PD-MCI were observed with the application of differing criteria. We propose that a 1.5SD cut-off score below premorbid functioning may provide greater utility in characterizing PD-MCI than a 1.5SD cut-off below normative data, which has been widely applied in previous studies examining the MDS PD-MCI criteria. Highlights: Substantial differences in PD-MCI frequencies with different sets of MDS criteria. Refinement of the MDS criteria is needed to standardize PD-MCI diagnosis. Characterization of PD-MCI should relate to decline from premorbid intellect. Clarification of an optimal cut-off point for characterizing MCI is needed.